Peran Model Evaluasi Scriven; Formatif-Sumatif dalam Meningkatkan Hasil Belajar PAI Siswa di SD Negeri Ngrukeman Bantul - Chaza Afida Amna; Wahyu Kholis Prihantoro; Aruni Qurrota A'yun; Al-Fath Faizal Syahbana; Lia Purwati (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Educational evaluation is crucial for assessing student success and the effectiveness of educational programs. Formative and summative evaluations have distinct objectives. Formative evaluation focuses on the ongoing learning process, while summative evaluation aims to assess the final learning outcomes. The Scriven model combines both types of evaluation to improve student learning outcomes. This article discusses the application of the Scriven model to improve Islamic Religious Education (PAI) learning outcomes at Ngrukeman Elementary School, Bantul. This study emphasizes the importance of evaluation in shaping students' character, developing their thinking, and enhancing social awareness. Educational evaluation aims to assess not only cognitive aspects but also affective and psychomotor aspects. With effective evaluation, teachers can identify students' strengths and weaknesses and design better learning. This contributes to improved student achievement and the overall quality of education. In this way, educational evaluation becomes a highly effective tool for improving and optimizing the learning process, ultimately supporting the achievement of comprehensive educational goals.